Lorenz Jaeger als Seelsorger

Einleitung - Priesching, Nicole; Kasprowski, Christian (Lorenz Jaeger als Kirchenpolitiker)

Einleitung - Priesching, Nicole; Pahlke, Georg (Lorenz Jaeger als Seelsorger)

„Ich klage an!“ Pfarrer Heinrich Ostermann am 19. Dezember 1945 an Erzbischof Lorenz Jaeger - Priesching, Nicole (Lorenz Jaeger als Seelsorger)

Beethoven in the House: Digital Studies of Domestic Music Arrangements - Page, Kevin R.; Kepper, Johannes; Siegert, Christine; Hankinson, Andrew; Lewis, David (Music Encoding Conference Proceedings 2021)
Performance of music in the home was the means by which most works were received before the advent of audio recordings and broadcasts, yet the notation sources that form our primary record of this culture have not been the subject of comprehensive or methodical study. Choices made by arrangers adapting music for domestic consumption – of instrumentation, abbreviation, or simplification – reflect the musical life of the 19th century, and can inform our understanding alongside contemporary accounts such as newspapers, adverts, and diaries. This position paper gives the background, motivation, and proposed approach of research currently being undertaken within the Beethoven in the House project. This will include a study of Steiner editions of Beethoven’s 7th and 8th Symphonies and Wellingtons Sieg, making a detailed comparison between arrangements, systematically identifying a core common to multiple versions, and asking if this reflects the stated values of the publisher. A second survey will look for patterns across a larger sample of lesser-known and poorly catalogued scores, collating emergent indicators of arrangers’ motivations within a narrative of the domestic market – the music industry of its day. Both studies will innovate digital methods which characterise arrangements as music encodings, including ‘sparse’ approaches to notation and annotation.
Keywords: BitH; mec-proceedings; mec-proceedings-2021

Encoding Genetic Processes II - Cox, Susanne; Kepper, Johannes (Music Encoding Conference Proceedings 2021)

A model for annotating musical versions and arrangements across multiple documents and media - Lewis, David; Shibata, Elisabete; Saccomano, Mark; Rosendahl, Lisa; Kepper, Johannes; Hankinson, Andrew; Siegert, Christine; Page, Kevin (9th International Conference on Digital Libraries for Musicology)
Keywords: BitH

‚Schreibsensibel‘ Geschichte unterrichten: Fachspezifische Textkompetenz als Gegenstand und Medium des historischen Lernens - Hartung, Olaf; Memminger, Josef (Schreiben fachübergreifend fördern. Grundlagen und Praxisanregungen für Schule, Unterricht und Lehrerinnen- und Lehrerbildung)

Editorial: Anschaulichkeit – Wissen. Macht. Alternativen. - Eckel, Julia; Linseisen, Elisa (Rabbit Eye – Zeitschrift für Filmforschung)
Keywords: Anschaulichkeit; Anschauung; Film; Epistemologie audiovisueller Medien; Erklärbarkeit; Anschauen; Sichtbarkeit; Unsichtbarkeit

Rabbit Eye: Anschaulichkeit (Rabbit Eye - Zeitschrift für Filmforschung)

Man nehme... den Konjunktiv. Verbformen in Kochrezepten - Wallmeier, Nadine (Praxis Deutsch)

Toward a Competence Model for Graphical Modeling - Soyka, Chantal; Schaper, Niclas; Bender, Elena; Striewe, Michael; Ullrich, Meike (ACM Transactions on Computing Education)
Modeling is an integral part of many computing-related disciplines and thus also represents a curricular core component in computing education in tertiary education. Competence models in which modeling is integrated at least to some extent already exist in some of these disciplines. However, for the core component of graphical modeling, a competence model that illuminates the relevant competences in detail is still lacking. Therefore, we develop a competence model for graphical modeling with the aim to make teaching and especially assessments in the field more competence-oriented. This paper reports on the first two studies conducted to develop and validate the competence model for graphical modeling. In the first study, the structure of the competence model was developed based on theories and approaches of educational science. Competences relevant for graphical modeling were deductively derived from literature and existing university course descriptions using techniques of qualitative content analysis. The result of the first study is a preliminary competence model. In the second study, the preliminary competence model was reviewed by means of an expert rating in the modeling community. The competence model was revised and refined based on these findings and subsequent expert discussions. The main result of the investigation represents the competence model for graphical modeling (CMGM), which includes a total of 74 competence facets at different cognitive process levels in the five content areas of ”model understanding and interpreting”, ”model building and modifying”, ”values, attitudes, and beliefs”, ”metacognitive knowledge and skills”, and ”social-communicative skills”.
Keywords: graphical modeling; conceptual modeling; computer science; competence model; higher education

Piloteinsatz einer E-Assessment-Plattform für die grafische Modellierung - Ullrich, Meike; Pfeiffer, Peter; Schiefer, Gunther; Soyka, Chantal; Stottrop, Tobias; Striewe, Michael; Fettke, Peter; Loos, Peter; Oberweis, Andreas; Schaper, Niclas (20. Fachtagung Bildungstechnologien (DELFI))

E-Assessment-Plattform für die grafische Modellierung - Ullrich, Meike; Pfeiffer, Peter; Schiefer, Gunther; Soyka, Chantal; Stottrop, Tobias; Striewe, Michael; Fettke, Peter; Loos, Peter; Oberweis, Andreas; Schaper, Niclas (20. Fachtagung Bildungstechnologien (DELFI))

Organisationen als Kompromissmaschinen: Zur Mikrofundierung von Organisationen im Neo-Institutionalismus und der Soziologie der Konventionen am Beispiel Sozialer Hilfen am Übergang von der Schule in den Beruf - Dahmen, Stephan (Steuerung von Bildungseinrichtungen. Theoretische Analysen erziehungswissenschaftlicher Organisationsforschung)

Regionales Sprechen und Schreiben

Techniken und Praktiken der Verdatung - Bender, Michael; Bubenhofer, Noah; Dreesen, Philipp; Georgi, Christopher; Rüdiger, Jan Oliver; Vogel, Friedemann (Diskurse – digital)

Screening zur Erfassung des Leseverständnisses in den Klassen 6 – 7 (SELV 6 – 7) - Seifert, Susanne; Maitz, Katharina; Riedl, Sylvia; Neumaier, Arnold; Stoff, Ilona; Gasteiger-Klicpera, und Barbara (Diagnostica)
Zusammenfassung. Im vorliegenden Beitrag wird das Screening zur Erfassung des Leseverständnisses für die Klassen 6 – 7 (SELV 6 – 7) vorgestellt, welches Leseverständnis während des Lesens mittels der Maze-Prozedur erfasst. Der Test liegt in einer Print- (SELV-P) und Digitalversion (SELV-D) vor. Es wurden 5 Paralleltestformen entwickelt. Zwei Studien zur Überprüfung der Reliabilität und Validität in den Klassen 6 und 7 werden präsentiert, wobei drei verschiedene Maze-Scorings (1: korrekt, 2: korrekt-inkorrekt, 3: korrekt / bearbeitet) einander gegenübergestellt werden. Studie 1 (SELV-P, n = 222, davon 85 6. Klasse) zeigt, dass die 4 Formen (ohne Form 3) die gleiche Fähigkeit messen, jedoch mit unterschiedlichen Mittelwerten. Der Einsatz als Lernverlauf-Messinstrument erscheint somit mit separaten Normen je Form möglich. Die Paralleltest- und Retestreliabilität dieser 4 Formen ist unter Verwendung von Score 1 und 2 ausreichend hoch, nicht aber bei Score 3. In Studie 2 (SELV-D, n = 345, davon 150 6. Klasse) wurde nur Form 1 betrachtet, die unter Verwendung aller 3 Scores die Kriterien der diskriminanten und konvergenten Validität erfüllt.
Keywords: Clinical Psychology

Diagnostik und Differenzierung - Seifert, Susanne; Paleczek, Lisa; Gasteiger-Klicpera, Barbara (Handbuch der sonderpädagogischen Diagnostik. Einführung in die Status- und Prozessdiagnostik sowie Förderplanung)

Vergleich unterschiedlicher Instrumente zur Messung von Gesundheitskompetenz im Zusammenhang mit Lesekompetenz und kognitiven Fähigkeiten von Jugendlichen - Seifert, Susanne; Maitz, Katharina; Pendl, Dominik; Gasteiger-Klicpera, Barbara (Diagnostica)
Zusammenfassung. Instrumente zur Messung von Gesundheitskompetenz bei Jugendlichen basieren auf sehr heterogenen Definitionen und Konzepten. Zudem können sie grundsätzlich in subjektive (Selbsteinschätzungs–) und objektive (die Performanz messende) Verfahren unterteilt werden. In der vorliegenden Studie wurden 2 subjektive (eHEALS; Kurzform des HLS-EU-Q16) und ein objektives Messinstrument (Claim) von 471 Jugendlichen der 6. und 7. Klassenstufe (Durchschnittsalter 13.04 Jahre; 49 % Mädchen; 63 % Familiensprache Deutsch) bearbeitet und auf ihren wechselseitigen Zusammenhang, den Zusammenhang mit kognitiven und Lesefähigkeiten, sowie Unterschiede in Bezug auf Geschlecht und Familiensprache untersucht. Das objektive Verfahren korrelierte nicht mit den subjektiven Verfahren. Dies bestätigt die Annahme, dass sie aufgrund der Messperspektive unterschiedliche Indikatorenausprägungen von Gesundheitskompetenz erfassen. Korrelationen mit Lese- und kognitiven Fähigkeiten zeigten sich nur beim objektiven Instrument, wohingegen die Selbsteinschätzungsinstrumente diese Aspekte der Gesundheitskompetenz nicht abbilden. Unterschiede hinsichtlich des Geschlechts und der Familiensprache zeigten sich insbesondere beim objektiven Instrument, allerdings sind Antwortverzerrungen bei Selbsteinschätzungen möglich. Die spezifischen Vor- und Nachteile von subjektiven und objektiven Verfahren sollten bei der Instrumentenauswahl berücksichtigt werden.
Keywords: Clinical Psychology